Bio-hydrogen production in an EGSB reactor under mesophilic, thermophilic and hyperthermophilic conditions - Abreu, A. A. (2007)
Mesophilic, thermophilic and hyperthermophilic bio-hydrogen production with an expanded granular sludge blanket (EGSB) fed with glucose and arabinose, without methane production, was demonstrated. Homoacetogenesis was observed on reactor when operated under mesophilic (37ºC) conditions but not under thermophilic (55ºC) and hyper-thermophilic conditions (70ºC). It was also found that under thermophilic and hyper-thermophilic conditions glucose is preferentially consumed than arabinose.